ANTIHYPERLIPIDEMIC AND HEPATOPROTECTIVE STUDIES ON LEAVES OF MACARANGA TANARIUS - Hendra, Phebe; Aurelia Jamil, Oktariani; Maharani, Dian Ayu; Suhadi, Maria Angelika; Yulanda Putri, Cyndi; Fenty; Julianus, Jeffry (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This Â study Â investigated Â the Â antihyperlipidemic Â and Â hepatoprotective Â effects Â of Â the Â hexane-ethanol Â fraction Â of Â methanol Â extract Â ofÂ Macaranga tanarius (HEM) in rats. Methods: The hexane-ethanol fraction was screened for toxicity by oral acute toxicity study. The antihyperlipidemic effect of the hexane-ethanol fraction and the unsolved of the hexane-ethanol fraction is measured against Wistar rats induced by glucose-fructose diets for 42 days through measuring serum cholesterol, triglyceride (TG), high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), and fasting blood glucose. The hepatoprotective effect of the hexane-ethanol fraction is determined against Wistar rats with liver damage induced by carbon tetrachloride through measuring serum glutamate pyruvate transaminase (SGPT), serum glutamate oxaloacetate transaminase (SGOT), alkaline phosphatase (ALP), albumin, lactate dehydrogenase (LDH), and total bilirubin. Results: There is no toxic effect that was observed on acute toxicity study. The TG, LDL-c, and fasting blood glucose levels were significantly (p<0.05) reduced after both of treatment the hexane-ethanol fraction and the unsolved HEM. Administration of the hexane-ethanol fraction 68.6 mg/kgBW significantly (p<0.05) prevented elevation of SGPT, SGOT, LDH, ALP, and decreasing of albumin level. Conclusion: The study showed antihyperlipidemic and hepatoprotective activities of the HEM in animal models. Keywords: Macaranga tanarius, Antihyperlipidemic, Hepatoprotective.